2014
DOI: 10.1152/ajpgi.00251.2014
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the umami taste receptor (T1R1/T1R3) initiates the peristaltic reflex and pellet propulsion in the distal colon

Abstract: Kendig DM, Hurst NR, Bradley ZL, Mahavadi S, Kuemmerle JF, Lyall V, DeSimone J, Murthy KS, Grider JR. Activation of the umami taste receptor (T1R1/T1R3) initiates the peristaltic reflex and pellet propulsion in the distal colon. Am J Physiol Gastrointest Liver Physiol 307: G1100 -G1107, 2014. First published October 16, 2014; doi:10.1152/ajpgi.00251.2014.-Intraluminal nutrients in the gut affect the peristaltic reflex, although the mechanism is not well defined. Recent evidence supports the presence of taste … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
54
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 49 publications
(81 reference statements)
2
54
1
Order By: Relevance
“…Stimulation of G-protein-coupled receptors results in an increase in intracellular calcium, and functional studies confirmed that tastants applied to entero-endocrine-derived cell lines caused a Ca-spike, and led to a release of peptides, including cholecystokinin (CKK; from STC-1 cells stimulated with bitter tastants) and glucagon-like peptide (GLP-1; from GLUTag cells stimulated by sweet tastants) (Wu et al, 2002; Jang et al, 2007). “Visceral behavioral” studies, using flat sheet preparations of live rodent colon, confirmed the direct role of entero-endocrine gustation in controlling gut motility (Kendig et al, 2014). Monosodium glutamate (MSG), a stimulant of the T1R1/T1R3 umami receptor, when applied to the colon preparations, elicited a peristaltic reflex, which was abolished in preparations from mice that were mutant for T1R1.…”
Section: Introductionmentioning
confidence: 88%
“…Stimulation of G-protein-coupled receptors results in an increase in intracellular calcium, and functional studies confirmed that tastants applied to entero-endocrine-derived cell lines caused a Ca-spike, and led to a release of peptides, including cholecystokinin (CKK; from STC-1 cells stimulated with bitter tastants) and glucagon-like peptide (GLP-1; from GLUTag cells stimulated by sweet tastants) (Wu et al, 2002; Jang et al, 2007). “Visceral behavioral” studies, using flat sheet preparations of live rodent colon, confirmed the direct role of entero-endocrine gustation in controlling gut motility (Kendig et al, 2014). Monosodium glutamate (MSG), a stimulant of the T1R1/T1R3 umami receptor, when applied to the colon preparations, elicited a peristaltic reflex, which was abolished in preparations from mice that were mutant for T1R1.…”
Section: Introductionmentioning
confidence: 88%
“…Video recording and spatiotemporal mapping of intestinal and colonic segments have been applied to a variety of species including zebrafish 26 , mouse 25,[27][28][29][30] , rat 7,9,[30][31][32][33] , guinea pig 5,6,8,[13][14][15][16][17][18][19]24,30,32,34,35 , brushtail possum 12,36 , rabbit 2,30,37,38 , chicken 39 , pig 40,41 and human 42 . The most widely studied species is the guinea pig.…”
Section: Discussionmentioning
confidence: 99%
“…The construction of STmaps and analysis of changes in motility pattern have been applied to key questions in the gastrointestinal motility of intestine and colon. These include: differentiation of neurogenic and myogenic contractions and defining the role of interstitial cells of Cajal 6,9,11,12,16,24,26,27,[29][30][31]33,[37][38][39][40]42 , understanding the complex interactions between the circular and longitudinal muscle layers 2,7,8,11,12,32,39,40 , examining the effects of intraluminal nutrients 10,18,19 , microbial strains 34 , and viscosities 12,36 on various motility patterns, and understanding the role of various endogenous neurohormonal agents and exogenous pharmacological agents 2,[4][5][6][7]9,10,[13][14][15][16][17]28,35,40 in the generation and modification of motility...…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The activation of T1R1/T1R3 expressed in the colon elicits the peristaltic reflex and pellet propulsion in mammals [24]. In regard to the gastrointestinal mGluRs, Akiba et al reported that mGluR1 and mGluR4 expressed in the duodenum regulate the duodenal mucosal defense to acidic stimulus [25].…”
Section: Discussionmentioning
confidence: 99%